Reassessment of chitosanase substrate specificities and classification. Issue 1 (December 2017) - Weikert, Tobias; Niehues, Anna; Cord-Landwehr, Stefan; Hellmann, Margareta; Moerschbacher, Bruno
Abstract Chitosanases can be used to produce partially acetylated chitosan oligosaccharides (paCOS) for different applications, provided they are thoroughly characterized. However, recent studies indicate that the established classification system for chitosanases is too simplistic. Here, we apply a highly sensitive method for quantitatively sequencing paCOS to reassess the substrate specificities of the best-characterized class I–III chitosanases. The enzymes' abilities to cleave bonds at GlcNAc residues positioned at subsite (−1) or (+1), on which the classification system is based, vary especially when the substrates have different fractions of acetylation (FA ). Conflicts with the recent classification are observed at higher FA, which were not investigated in prior specificity determinations. Initial analyses of pectin-degrading enzymes reveal that classifications of other polysaccharide-degrading enzymes should also be critically reassessed. Based on our results, we tentatively suggest a chitosanase classification system which is based on specificities and preferences of subsites (−2) to (+2). Chitosanases are classified according to their specificity in cleaving bonds at GlcNAc residues but the current system may be too simplistic. Here, the authors use quantitative mass spectrometry to revisit chitosanase specificity and propose additional determinants for their classification.